Influence of Exposure at Different Altitudes on the Executive Function of Plateau Soldiers—Evidence From ERPs and Neural Oscillations - Wei, Xin; Ni, Xiaoli; Zhao, Shanguang; Chi, Aiping (Frontiers in Physiology, 2021)
Investigate the changes in soldiers’ brain executive function at different altitude environments and their relationship with blood oxygen saturation. Stratified sampling in different high altitude 133 active-duty soldiers, who were stationed in Weinan (347m, n = 34), Nyingchi (2950m, n = 32), Lhasa (3860m, n = 33), and Nagqu (4890m, n = 34) for two years. The Go/NoGo paradigm with event-related potentials (ERPs) and event-related oscillations（EROs）was used to explore the time course and neural oscillation courses of response inhibition. Behavioral results revealed that at the 4890m altitude area, the soldiers had the highest false alarm rate of successfully inhibit NoGo stimulation, the longest reaction time, and the slowest information transmission rate. Electrophysiological results found that NoGo-N2 and N2d in the middle frontal lobe more positive with altitude and changed significantly at 3860m; The amplitudes of NoGo-P3 and P3d in 2950m, 3860m, and 4890m were significantly more negative than those in the plain and changed significantly at 2950m. The results of correlation analysis showed that NoGo-P3 was negatively correlated with altitude (r = -0.358, p = 0.000), positively correlated with SpO2 (r = 0.197, p = 0.041) and TIR (r = 0.202, p = 0.036). P3d was negatively correlated with altitude (r = -0.276, p = 0.004) and positively correlated with TIR (r = 0.228, p = 0.018). N2d was negatively correlated with TIR (r = 0.204, p = 0.034). The power spectrum analysis of NoGo-N2 and NoGo-P3 phases showed that the power of δ and θ bands at 2950m, 3860m, and 4890m area was significantly lower than the plain area and showed a significant step-by-step decrease (2950m<3860m<4890m); The α-band (8-14Hz) power increases significantly only in the area of 4890m altitude. These findings show that different elevations had significant effects on the executive brain function of soldiers, in which 3860m was the injury height in the conflict monitoring stage of brain response inhibition function, and 2950m was the injury height in the response inhibition stage. Besides, military personnel’s brain executive function is closely related to SpO2, and the decrease of SpO2 will lead to greater response inhibition of the military brain.